Today is your day inspiration to make you win every time - Gogna, Arun (Arun Gogna, 2011)
In this newest collection of enlightening stories, Catholic lay preacher Arun Gogna speaks straight to your heart, bringing you truths to live by, accompanied with his signature humor and wisdom.